The EFFECTS OF COVID-19 ON FOOD SECURITY STATUS OF RURAL FARMING HOUSEHOLDS. EVIDENCE FROM NIGERIA: EFFECTS OF COVID-19 ON FOOD SECURITY STATUS OF RURAL FARMING HOUSEHOLDS - Mukaila, Ridwan; Falola, Abraham; Omotesho, Abayomi O.; Akanbi, Sheu-Usman O.; Egwue, Lynda O.; Aidi, Hakeem O. (Journal of Agricultural Sciences (Belgrade), 2024)
For the past couple of decades, food insecurity is a major global phenomenon which makes zero hunger the second Sustainable Development Goal. Despite this, COVID-19 set-in and posed a serious threat to the food system. Thus, the need to assess its effect on food security arises. This study, therefore, examined the effects of COVID-19 on rural farming households’ food security in Enugu State, Nigeria. Data collected from 120 households were analysed using food security index, logistic regression and Likert rating scale. The results revealed that the majority (64.5%) of the households were food insecure with a shortfall index of 0.313 while only 35.5% were food secure with a surplus index of 0.109. The average daily adult equivalent calorie consumption of food insecure and food secure households were 1552.52 and 2506.88 kcal, respectively. Low availability of food (p
Keywords: COVID-19; food insecurity; rural households; smallholder farmers; coping strategies